Integrasi Pendidikan Agama Islam: Kecerdasan Spiritual dan Emosional melalui Kitab Mahfudzot untuk Menumbuhkan Akhlak - Sofa, Ainur Rofiq; Mundir, Mundir; Ubaidillah, Ubaidillah (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
This study investigates the integration of spiritual and emotional intelligence in Islamic religious education at Zainul Hasan Genggong Islamic University, recognizing the urgent need for moral development amid contemporary challenges, particularly the increase of promiscuity among adolescents. Using a qualitative approach involving observation, in-depth interviews, and documentation, this study aims to explain the impact of this integration on student moral formation. Research findings show that integrating spiritual and emotional intelligence facilitated through Hablum MinAllah and Hablum Minannaas processes significantly contributes to the ethical development of students at Zainul Hasan Genggong Islamic University. In particular, educational materials such as Mahfudzot Fadoilul Iman, Mahfudzot Fadhoilun Nabi Wa Ash Shahabah, and Genggong Pesantren Philosophy play a central role in this comprehensive educational approach. In conclusion, the study identified three primary outcomes: the substantial influence of spiritual and emotional intelligence in shaping student morale, the interrelated nature of the selected educational material, and the adoption of the Tikrar Method in Mahfudzot to cultivate Spiritual and Emotional Intelligence. It emphasizes the strategic repetition of Quranic principles in Islamic Religious Education subjects as an effective means of instilling and strengthening positive values among Zainul Hasan Genggong Islamic University students.